PROFESSIONAL TRAINING OF FUTURE MASTERS IN PRESCHOOL EDUCATION IN CONDITIONS OF MARTIAL LAW - Dychkivska, Ilona; Kozliuk, Olha (Theoretical and Methodical Problems of Children and Youth Education, 2023)
The article is devoted to the problem of professional training of future specialists in preschool education at the second (Master’s degree) level of higher education in conditions of martial law. It emphasizes that dynamism, innovative forms and methods of teaching Master’s students characterize the modern education system, and, therefore, it requires updating and incorporating modern disciplines into educational and professional programs aimed at ensuring professional mobility, “soft skills”, innovative-communicative competence, and the ability to solve complex professional tasks. The aim of the article is to highlight the experience of the Department of Preschool Pedagogy and Psychology and Special education named after prof. T. I. Ponimanska, in training Master’s students in Preschool Education at Rivne State University of Humanities in conditions of martial law. The article provides a detailed analysis of the changes made to the educational and professional program, taking into account the requirements of the higher education standard for the second (Master’s degree) level of higher education in the field of Preschool Education (specialty 012) and the professional standard “Head (Director) of a Preschool Education Institution”. It also discusses the peculiarities of organizing the educational process in conditions of martial law and the changes introduced to the educational components, considering contemporary requirements. The presentation of the article’s material relies on the extensive use of theoretical methods such as problem-targeted, logical-systemic, and structural-functional analysis, as well as specific search methods including synthesis, forecasting, and generalization. The article concludes that the preparation of future Masters in Preschool Education, as well as directors of preschool institutions, requires fundamental changes and a comprehensive approach. Additionally, the preparation should have an integrated nature and practical orientation, encompassing both theoretical knowledge and practical skills, ensuring the psychological and physical well-being of children, and facilitating effective communication with parents and other professionals responsible for child safety. Future Masters in Preschool Education can effectively work in various conditions, including those of martial law, ensuring the safety and holistic development of children in preschool institutions with only proper training and support for the development of professional skills. Furthermore, using modern technologies, electronic resources, and distance learning tools is relevant, as they are important means of education and communication in today’s world. They allow Masters to access up-to-date information, interact with professionals from different fields and countries to exchange experiences, and learn from the best experts in the field of preschool education. The article’s material will be useful for scientific and pedagogical workers of institutions of higher education and departments that train students of higher education at the second (Master’s degree) level of higher education in order to include experience of national institutions of higher education for the development of their own educational and professional programs.